Nrf2 expression modifies influenza A entry and replication in nasal epithelial cells - Kesic, Matthew J.; Simmons, Steven O.; Bauer, Rebecca; Jaspers, Ilona (Free radical biology & medicine, 2011)
Influenza infection is a major cause of morbidity and mortality worldwide, especially during pandemics outbreaks. Emerging data indicate that phase II antioxidant enzyme pathways could play a role in virus-associated inflammation and immune clearance. While Nrf2-dependent gene expression is known to modify inflammation, a mechanistic role in viral susceptibility and clearance has yet to be elucidated. Therefore, we utilized differentiated human nasal epithelial cells (NEC) and an enzymatic virus-like particle entry assay, to examine the role Nrf2-dependent gene expression has on viral entry and replication. Herein, lentiviral vectors that express Nrf2-specific short hairpin (sh)-RNA effectively decreased both Nrf2 mRNA and Nrf2 protein expression in transduced human NEC from healthy volunteers. Nrf2 knockdown correlated with a significant increase in influenza virus entry and replication. Conversely, supplementation with the potent Nrf2 activators sulforaphane (SFN) and epigallocatechin gallate (EGCG) significantly decreased viral entry and replication. The suppressive effects of EGCG on viral replication were abolished in cells with knocked-down Nrf2 expression, suggesting a causal relationship between the EGCG-induced activation of Nrf2 and the ability to protect against viral infection. Interestingly, the induction of Nrf2 via nutritional supplements SFN and EGCG increased antiviral mediators/responses: RIG-I, IFN-β, and MxA at baseline in the absence of infection. Our data indicate that there is an inverse relationship between the levels of Nrf2 expression and the viral entry/replication. We also demonstrate that supplementation with Nrf2-activating antioxidants inhibits viral replication in human NEC, which may prove to be an attractive therapeutic intervention. Taken together, these data indicate potential mechanisms by which Nrf2-dependent gene expression regulates susceptibility to influenza in human epithelial cells.